State of the Art Review of Active and Passive Knee Orthoses - Agustín Barrera Sánchez; Andrés Blanco Ortega; Eladio Martínez Rayón; Fabio Abel Gómez Becerra; Arturo Abúndez Pliego; Rafael Campos Amezcua; César Humberto Guzmán Valdivia (Machines, 2022)
The use of specialized devices, such as orthopedic devices, has become indispensable in the lives of people with disabilities since ancient times. The primary purpose of such devices is to perform activities and solve problems that afflict their bearers in any extremity of their body. One of the most recurrent problems occurs in the lower extremities regarding mobility and autonomy. In addition, the use of orthopedic devices is considered a tool to lighten the repetitive and heavy rehabilitation work of physiotherapists while improving the patient’s recovery efficiency. A significant challenge is that a great variety of these devices are similar in their design and manufacture, complicating their application in rehabilitation processes. For these reasons, this article aims to provide an overview of the features and considerations made in the architecture of orthosis designs, emphasizing lower extremity orthoses for the case of knee joint analysis. A literature review of active and passive knee orthoses manufactured from the 1970s to the present was carried out, considering aspects such as manufacturing materials, mechanical systems, types of actuators, and control strategies. This review shows that the designs and development of orthoses have been abundant in these devices for lower limbs. Based on the literature collected, we have studied the main robotic devices focusing on the characteristics of design, manufacturing, and control systems to assist in human locomotion and support in rehabilitation processes.